SAR Bathymetry Review and Its Possibility Implementation in Indonesia - Koman, Wening Aisyah Fauziana; Basith, Abdul; Julzarika, Atriyon (Jurnal Geospasial Indonesia, 2023)
Indonesia needs bathymetry information for diverse applications as a maritime country. There are various methods of determining the water depth for bathymetry. The advancement of satellite imagery data has led to the increasing use of remote sensing data for depth measurements. With satellite imaging, wide area coverage can be achieved in a relatively short time, making depth data acquisition more cost-effective. SAR (Synthetic Aperture Radar) imagery is an active remote sensing technology developed to estimate depth data known as the SAR Bathymetry method. This method is still not widely applied, especially in Indonesia, even though it has considerable potential with cloud-free imageries, where it becomes a severe problem in tropical countries when using optical imagery. Therefore, this paper will discuss algorithms and techniques for depth data estimation using SAR Bathymetry and their possible implementation in Indonesia. The optimum depth, SAR image recommendation, and conditions required to apply this method will also be discussed.